Sosialisasi Pencegahan Hipertensi dan Anemia Ibu Hamil: Socialization of Prevention of Hypertension and Anemia in Pregnant Women - Pratiwi, Liliek; Nawangsari, Harnanik (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Gestational hypertension typically arises after the 20th week of pregnancy and resolves postpartum. Key risk factors include obesity and diabetes mellitus, and when accompanied by protein in the urine, it may lead to preeclampsia. Pregnant women must recognize early signs of preeclampsia to safeguard both maternal and fetal health. Anemia in pregnant women is also prevalent in West Java, exacerbating the risks of low birth weight and maternal mortality. This study utilized a collaborative approach, emphasizing a pentahelix model involving government, academia, professional organizations, media, and business sectors to enhance health promotion activities. The intervention focused on the socialization of hypertension and anemia prevention among pregnant women, aiming to reduce maternal and infant mortality rates. The socialization efforts significantly raised awareness among pregnant women about the risks of hypertension and anemia, along with the importance of early detection and preventive measures. Data from healthcare professionals indicated increased community engagement in maternal health programs, showing a promising trend in reducing related complications. The collaboration across various sectors has shown positive outcomes in promoting the prevention of hypertension and anemia in pregnancy. Continuing these efforts, particularly through health education and community involvement, is crucial for reducing maternal mortality and improving maternal and fetal health outcomes.